Characteristics of Chinese Food Culture Documentary Communication in the New Century and Its Implications - Xia, Jing; Niyomrit, Dr. Varangkana (Journal of Dhamma for Life, 2025)
The purpose of this paper is to study the communication characteristics and enlightenment of Chinese food culture documentary in the new century. Since 2000, under the background of cultural industrialization transformation, Internet communication and mass cultural consumption, the communication of Chinese food culture documentary has become a prominent cultural communication phenomenon. This paper takes Chinese food culture documentary in the new century as the research object, sets the target in multi-dimension and multi-method for three-dimensional consideration, explores the communication characteristics and enlightenment of Chinese food culture documentary in the new century, and hopes to provide reasonable suggestions for the development of documentary culture communication in the future. The findings are as follows: 1. Multiple features of the connotation of Chinese food culture documentaries in the new century. 2. Characteristics of the compound framework of documentary communication of Chinese food culture in the new century 3. Enlightenment of documentary communication of Chinese food culture in the new century.